Foreign currency financial reporting from euros to yen to yuan a guide to fundamental concepts and practical applications - Rowan, Robert (Robert J.), 1966- (Wiley and SAS business series, 2011)
"As the world is becoming a smaller place and more and more companies take part in global transactions, the reporting of foreign currency has become an issue. Companies must report their foreign currency transactions on their financial statements. This book will provide a primer on how to report foreign currency transactions as well as guidance on building a computer program for such reporting. Written in a user-friendly style, this book will focus on the fundamental concepts of foreign currency transactions. The foundation provided in this book will allow corporations to accurately and consistently report past transactions and also allow them to look into the future to forecast and foresee the impacts that changing exchange rates could have on their businesses"--